2000
DOI: 10.1073/pnas.97.20.11056
|View full text |Cite
|
Sign up to set email alerts
|

Experimental diabetes in rats causes hippocampal dendritic and synaptic reorganization and increased glucocorticoid reactivity to stress

Abstract: We report that 9 d of uncontrolled experimental diabetes induced by streptozotocin (STZ) in rats is an endogenous chronic stressor that produces retraction and simplification of apical dendrites of hippocampal CA3 pyramidal neurons, an effect also observed in nondiabetic rats after 21 d of repeated restraint stress or chronic corticosterone (Cort) treatment. Diabetes also induces morphological changes in the presynaptic mossy fiber terminals (MFT) that form excitatory synaptic contacts with the proximal CA3 ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
162
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(172 citation statements)
references
References 63 publications
9
162
0
1
Order By: Relevance
“…Adult male Sprague-Dawley rats were purchased from Charles River Laboratories and housed individually for a minimum of 2 weeks before the start of experiments. Streptozocin was administered via the femoral vein at a dose of 70 mg kg -1 as described 16 . In order to be included in the study, STZ-treated rats were required to exhibit serum glucose levels ≥ 200 mg dL -1 .…”
Section: Animals and Surgerymentioning
confidence: 99%
“…Adult male Sprague-Dawley rats were purchased from Charles River Laboratories and housed individually for a minimum of 2 weeks before the start of experiments. Streptozocin was administered via the femoral vein at a dose of 70 mg kg -1 as described 16 . In order to be included in the study, STZ-treated rats were required to exhibit serum glucose levels ≥ 200 mg dL -1 .…”
Section: Animals and Surgerymentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14]26 Corticosteroids have also been shown to increase the likelihood of neuronal death in rat embryonic hippocampal cultures. 27,28 In the present experiments, hippocampal cell cultures were prepared from postnatal rats, aged 4-5 days.…”
Section: Model Validationmentioning
confidence: 99%
“…4,5 The detrimental effects of corticosteroids on the hippocampus are backed by imaging studies in humans: there is a strong negative correlation between cortisol levels and hippocampal volume in patients with major depression 6,7 and in subjects with Cushing's disease; 8 reduced hippocampal volumes were also recently found in rats treated with dexamethasone (DEX), a GR agonist. 9 While most of the hippocampal shrinkage observed may be due to neuritic atrophy, including dendritic impoverishment and synaptic loss, [10][11][12] other experiments have demonstrated that GR activation activates a molecular cascade, leading to significant levels of neuronal cell death through apoptotic mechanisms. 13 Besides apoptosis of mature hippocampal neurons, 14 there is also evidence that GRs interfere with proliferation of granule neurons of the dentate gyrus.…”
mentioning
confidence: 99%
“…Hippocampal neurons are also sensitive to the effects of diabetes Magariños & McEwen, 2000) and often show damage to presynaptic and postsynaptic structures, dysregulation of calcium homeostasis, neuronal loss, dendriticatrophy in CA3 neurons, reduced expression of insulin growth factors and their receptors, and decreased neurogenesis (Jackson-Guilford et al; Magariños & McEwen;Li et al, 2002aLi et al, , 2002bKlein & Waxman, 2003;Saravia et al, 2002).…”
Section: Introductionmentioning
confidence: 99%